THE RELATIONSHIP BETWEEN STRESS AND THE SLEEP QUALITY OF HEALTH WORKERS DURING THE COVID 19 PANDEMIC - Priskila Sekar Dharana Tantadiputra; Paulus Alexander Supit; Tabita Novita Anggriani (JOURNAL OF WIDYA MEDIKA JUNIOR, 2023)
Psychological stress is the body’s way to cope with stressors. We are not able to evade stressors. In fact, we need stressors to keep ourselves going. So stress to an extent is a good thing. It is harmful when it becomes a distress, in which it starts to affect our bodily function, including our sleep quality. Psychological stress will activate the body’s HPA-axis and the sympathetic pathway of the autonomic nervous system, releasing hormones such as Cortisol and Catecholamine. These hormones can cause the disturbance of sleep. The aim of this study is to find the relation between the level of stress and the sleep quality in healthcare workers during the COVID-19 pandemic. PSS (Perceived Stress Scale) was used to calculate the level of stress and PSQI (Pittsburgh Sleep Quality Index) was used to calculate sleep quality. In this study we found that the level of stress is related to sleep quality in healthcare workers during the COVID-19 pandemic. The relation is positive, significant (P = 0.002), and moderate (r = 0.4). To conclude, there is a relation between stress and sleep in healthcare workers during the COVID-19 pandemic.